2020
DOI: 10.3390/foods9101458
|View full text |Cite
|
Sign up to set email alerts
|

Legume Beverages from Chickpea and Lupin, as New Milk Alternatives

Abstract: Recently, milk consumption has been declining and there is a high demand for non-dairy beverages. However, market offers are mainly cereal and nut-based beverages, which are essentially poor in protein (typically, less than 1.5% against the 3.5% in milk) and are not true milk replacers in that sense. In this work, new beverages from different pulses (i.e., pea, chickpea and lupin) were developed using technologies that enable the incorporation of a high level of seed components, with low or no discharge of by-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…Similar studies on the chickpea protein hydrolysates produced using GI enzymes and bromelain could be beneficial in producing a novel ingredient. Another study evaluated chickpea “milk” as a plant-based alternative to milk and hypothesized that the use of enzymes could be beneficial in modifying the final product and be a useful method in the optimization of the process [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies on the chickpea protein hydrolysates produced using GI enzymes and bromelain could be beneficial in producing a novel ingredient. Another study evaluated chickpea “milk” as a plant-based alternative to milk and hypothesized that the use of enzymes could be beneficial in modifying the final product and be a useful method in the optimization of the process [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the manufacturing of the non-dairy milk alternative, this technique is mostly used for homogenization and emulsification [57]. The optimization of colloidal milling process parameters improves the physical stability of non-dairy milk alternatives by efficiently reducing the size of dispersed particles [58]. Different studies have shown that the amount of water added for wet milling depends on the kind of raw material, for instance, almond milk (1:9; almond& water), Sesame (1:5; sesame & water), Peanut (1:9; Peanut: water), soybean (1:5; soy: water) [15,36,37,59].…”
Section: Wet Milling or Grindingmentioning
confidence: 99%
“…Innovative food products also include a whole range of products based on legume protein such as vegan ice cream or vegan yoghurts (e.g. Lim et al, 2019) and drinks (Qamar et al, 2019;Lopes et al, 2020;Nawaz et al, 2020;Verni et al, 2020). Also a high diversity of spreads has been and is being developed.…”
Section: Legumes As Innovative Food Ingredientmentioning
confidence: 99%